Assessment of Dietary Habits in Pregnant Women Attending Primary Health Care Centers - Hamza Wanas, Doaa; Ismael Mansoor, Haqi (Kerbala Journal of Nursing and Health Sciences., 2025)
Introduction :Pregnancy is the greatest critical and nutritionally demanding phase in a female's lifespan. Overall increased need for nutrients to facilitate power storage as new tissue, the expansion of established mother organs such as the breasts and uterus, and the increased energy demands for tissue synthesis make expectant women more susceptible to inadequate nutrition. Dietary habits are characterized as visible actions or behaviors related to eating patterns and can be categorized as beneficial or detrimental dietary practices. Nutritional deficits resulting from dietary habits and patterns are more prevalent while pregnant than at any other life phase.This study assessed dietary habits and associated factors among pregnant women attending primary health care centers in Najaf. Methods: A cross-sectional analytical research was performed from November 19, 2024 to March 10, 2025, including 150 pregnant women receiving prenatal services at primary health care clinics in Najaf city. Six centers were chosen using basic random selection. A questionnaire was utilized to collect data, which included socio-demographic information, reproductive health, body mass index, and dietary habits. Result: The results showed no statistically significant associations between dietary habits and sociodemographic variables, including (age group, education level, occupation, monthly income , and residency) (p = 0.497 , 0.800, 0.744, 0.630, 0.823). A significant association was found between gestational age and dietary habits (p = 0.034), with poor dietary practices reported in 90.12% of women in the third trimester, 80.39% in the second trimester, and 66.67% in the first trimester. No significant associations were observed with gravidity, parity, type of pregnancy, abortion history, birth interval, or medical visits (p > 0.05). Dietary habits also showed no significant relationship with BMI (p = 0.620), although poor habits were prevalent among overweight (85.29%) and obesity class II (100%) participants. Overall, 84.0% of pregnant women exhibited poor dietary habits, with a mean score of 1.60 ± 0.367, while only 16.0% demonstrated a moderate level. The study found that most pregnant women had poor dietary habits, mainly linked to gestational age, with worse practices in later pregnancy. Irregular meal timing, meal skipping, and food avoidance showed a lack of nutritional awareness.